INCONCLUSIVE FAMILY OWNERSHIP IN FAMILY BUSINESS: NARRATIVE LITERATURE REVIEW AND FUTURE RESEARCH - Widayanti, Rochmi; Hasan, Shaddam (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article presents a narrative literature review on the role and implications of family ownership in family businesses. Despite their global prevalence, the relationship between family ownership and firm performance remains inconclusive. The review synthesizes empirical findings from various countries, particularly in Asia and Europe, illustrating that family-controlled firms differ significantly in structure and performance due to cultural, legal, and institutional factors. While some studies show that family ownership enhances firm performance—especially when family members are actively involved in management—others suggest that excessive ownership may hinder value creation due to entrenchment and expropriation risks. The analysis highlights the dual perspectives of agency theory: interest alignment and entrenchment effects. The findings also underline the importance of succession planning and intergenerational leadership in sustaining long-term firm performance. This review concludes by emphasizing the need for further research to determine optimal ownership thresholds and contextual factors that influence the effectiveness of family ownership across different regions and development stages